Utilization of ICT-based Learning Media: Differentiated learning in SDGs - Chodijah, Siti; Al-Fahad, Muhamad Firman; Ekowati, Ainiyah; Risyana, Ariq Fauzan (Pedagonal : Jurnal Ilmiah Pendidikan, 2024)
This research is motivated by the need for ICT (Information and Communication Technology) based learning media that should be taken seriously in learning. In addition, it is sustainable with the orientation of the SDGs (Sustainable Development Goals) in education, namely Goal 4: Quality education - Ensure appropriate and inclusive quality education and encourage lifelong learning opportunities for all people, and promote education for sustainable development. The purpose of this research is to analyze how the utilization of media in learning, the fulfilment of learning media according to the needs of students with differentiated SDGs (Sustainable Development Goals) with ICT-based learning media (Information and Communication Technology), and analysis of problem solving that will be met by alternative solutions in learning media literature. This research uses a qualitative approach with descriptive methods. Data collection was conducted using purposive sampling technique by determining the sample based on certain considerations. The sample in this study was 144 students from various levels spread across Greater Bogor. Based on the results of the research that has been conducted, it can be described that Information and communication technology in learning has not been fully utilized by teachers. This has an impact on the work produced by students through media utilization. The utilization of learning media based on information and communication technology (ICT) fosters the active role of students in working on learning. It can be concluded that using ICT-based learning media could lead the students to optimize their learning outcome, skills through differentiated learning pertaining to SDGs.